An efficiency model and optimal control of the vehicular diesel exhaust heat recovery system using an organic Rankine cycle. (15th March 2019) - Yang, Can; Wang, Weiye; Xie, Hui
Abstract: Recovering and converting the vehicular exhaust to mechanical or electrical energy using an organic Rankine cycle (ORC) is a hotspot in recent years. But due to the highly transient exhaust conditions in real driving cycles, how to control the ORC systems is still a big problem. In this paper, the dynamic, multi-modes, and coupling problems, which are obstacles for the ORC system control, are analyzed at first. Subsequently, a control structure, making some sort of compromise, is put forward, which focuses more on the system operation continuity, gain-loss balance, but not just pursuing the cycle efficiency optimality, wherein a systematic efficiency model, taking evaporating and condensing pressures as variables, is the heart. Seeing that the efficiency model is a binary nonlinear model, an order reduction method is presented to solve the model at an acceptable computational cost. Finally, control performances are demonstrated outstanding in the simulation on the Highway Fuel Economy Test (HWFET) cycle. Despite very transient exhaust gas conditions, the fluid before the turbine keeps always superheated 5 K-15 K. The power-production mode accounts for 94% of the whole duration, and undesirable start-stop procedures are fully avoided. The useful power coefficient achieves more than 80%. Highlights: A control structure is proposed to handle the dynamic, multi-modes and coupling problems. A control-oriented system efficiency model is established and verified to be viable. Evaporating and condensing pressures are controlled satisfactorily in dynamic simulation on HWFET cycle.